Organic electrode material, preparation method thereof and high-performance aqueous aluminum ion battery
The new organic electrode material synthesized through one-step dehydration and condensation reaction solves the problems of active site limitation, structural instability and redox kinetics in the positive electrode applications of traditional organic materials, and achieves high specific capacity and circulation The electrochemical properties of stability and rate performance are suitable for large-scale promotion.
Patent Information
- Application Number
- CN202411701169.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-26
Smart Images

Figure CN119462656A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, and in particular to an organic electrode material and a preparation method thereof, and a high-performance aqueous aluminum ion battery. Background Art
[0002] As the increasing cost, environmental unfriendliness and safety risks of lithium-ion batteries have become increasingly prominent, thus limiting their further development, aqueous rechargeable batteries based on non-flammable electrolytes have received more attention, such as aluminum-ion batteries. According to the known situation, aluminum metal content currently ranks first among metals, and rechargeable aluminum-ion batteries (AIBs) have high theoretical capacity and Al 3+ / Al has favorable potential, so it also gives it huge large-scale energy storage capacity.
[0003] At present, electrode materials are divided into organic electrode materials and inorganic electrode materials. Inorganic electrode materials have the characteristics of high specific capacity, but they have limited resources and easy structural collapse. In addition, the huge application market also poses major challenges to the sustainability and cost of inorganic electrode materials (especially positive electrode materials). Organic electrode materials, due to their rich carbon, hydrogen, oxygen and other elements, have the advantages of being renewable, green, low-cost and high-capacity. Therefore, they have begun to receive widespread attention in recent years. That is, aluminum batteries using organic electrode materials provide an attractive way for sustainable and large-scale energy storage.
[0004] Previous studies have shown that the materials used in aluminum battery positive electrodes need to consider the following factors:
[0005] 1. Can the electrochemical performance indicators of the material, such as energy density, power density and cycle life, meet the requirements of practical applications?
[0006] 2. What are the cost, resource availability, and thermal / chemical stability of electrode materials for large-scale electrochemical energy storage applications?
[0007] However, traditional organic materials cannot meet the above requirements well due to their limited active sites, structural instability and slow redox kinetics. That is, the application of traditional organic materials in the positive electrode of aluminum batteries has great limitations and is difficult to promote and apply on a large scale. Summary of the invention
[0008] The present invention discloses an organic electrode material and a preparation method thereof and a high-performance aqueous aluminum ion battery, which can solve the problem that when traditional organic materials are applied to the positive electrode of aluminum batteries, they are greatly restricted due to defects such as limited active sites, structural instability and redox kinetics.
[0009] The technical solution adopted by the present invention is as follows:
[0010] One of the purposes of the present invention is to provide an organic electrode material, the molecular structure of which is:
[0011]
[0012] The second object of the present invention is to provide a method for preparing the above-mentioned organic electrode material, which is obtained by a one-step dehydration condensation reaction of 1,10-phenanthroline-5,6-dione and 2,3-diaminonaphthalene-1,4-dione.
[0013] Specifically, the specific process of the one-step dehydration condensation reaction is as follows:
[0014] Step 1: adding 1,10-phenanthroline-5,6-dione and 2,3-diaminonaphthalene-1,4-dione to an ethanol / acetic acid solution with a volume ratio of 1:1, and ultrasonically treating until the solid matter is completely dissolved to obtain a mixed solution; the molar ratio of the 1,10-phenanthroline-5,6-dione to the 2,3-diaminonaphthalene-1,4-dione is 0.8-1:1-1.2;
[0015] Step 2: Stir and heat the mixed solution to allow 1,10-phenanthroline-5,6-dione and 2,3-diaminonaphthalene-1,4-dione to react completely, and then cool to room temperature;
[0016] Step 3: The solution obtained in step 2 is filtered to obtain the target solid, which is then washed and dried to obtain the organic electrode material.
[0017] Furthermore, in step 2, the reaction conditions are 70-80° C. and 150-200 rpm.
[0018] Furthermore, in step 3, after the suction filtration, the target solid is washed with ethanol, acetic acid and water in sequence.
[0019] The third object of the present invention is to provide a high-performance aqueous aluminum ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode is made of the organic electrode material described in claim 1.
[0020] Specifically, the preparation process of the positive electrode is as follows:
[0021] Step a: mixing and grinding an organic electrode material, a conductive agent and a binder in a weight ratio of 7:2:1 to form a uniform slurry;
[0022] Step b: The slurry is evenly coated on the titanium foil current collector, and then dried to obtain the positive electrode.
[0023] Furthermore, the step a is specifically as follows: weighing the organic electrode material, the conductive agent and the binder respectively and putting them into an agate mortar, then dropping 2-5 ml of N-methyl-2-pyrrolidone therein, and continuously grinding to form a uniform slurry.
[0024] Preferably, the conductive agent is Ketjen black.
[0025] Preferably, the binder is polyvinylidene fluoride.
[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0027] (1) 1,10-phenanthroline-5,6-dione is mainly used to prepare molecules with specific functions, synthesize drug precursors, catalytic reaction materials, etc. Due to the presence of two pyridine ligands, 1,10-phenanthroline-5,6-dione can form stable complexes with a variety of transition metals. These metal complexes can act as catalysts in chemical reactions to promote specific transformation processes. The present invention utilizes the above-mentioned properties of 1,10-phenanthroline-5,6-dione and applies it to organic electrode materials. The present invention designs the component ratio and reaction parameters to allow it to undergo a one-step dehydration condensation reaction with 2,3-diaminonaphthalene-1,4-dione in a highly polar organic solvent, thereby constructing a new type of organic electrode material. The organic electrode material structure constructed by the present invention has a large number of abundant C=N bonds and C=O bonds, which can be used as cation storage sites; at the same time, experiments show that the organic electrode material also has a small charge transfer impedance and a high ion diffusion coefficient, indicating that it has fast redox kinetics and can achieve reversible storage of cations. Therefore, based on the above characteristics, when this kind of organic electrode material is used as the positive electrode material of aqueous aluminum ion batteries, it can exhibit very high specific capacity, excellent cycle stability and rate performance, making the aqueous aluminum ion battery have excellent electrochemical properties.
[0028] (2) The organic electrode material prepared by the present invention is not only low in raw material cost and environmentally friendly, but also prepared by a one-step dehydration condensation reaction technology, with a simple preparation process, no need for multiple purifications, and ensures high purity and structural consistency of the product. Therefore, the present invention provides a feasible strategy for realizing the green and low-cost application of organic materials in aluminum ion batteries, which has a very good application prospect and is very suitable for large-scale promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a schematic diagram of the synthesis of the organic electrode material obtained in Example 1 of the present invention.
[0030] Figure 2 This is the Fourier transform infrared spectrum of the organic electrode material obtained in Example 1 of the present invention.
[0031] Figure 3 This is the thermogravimetric analysis diagram of the organic electrode material obtained in Example 1 of the present invention.
[0032] Figure 4 This is a scanning electron microscope image of the organic electrode material obtained in Example 1 of the present invention.
[0033] Figure 5 The aluminum ion battery in Example 3 of the present invention is at 0.1mV·s -1 Cyclic voltammetry curves at different scan rates.
[0034] Figure 6 This is a rate performance diagram of the aluminum ion battery in Example 3 of the present invention.
[0035] Figure 7 The aluminum ion battery in Example 3 of the present invention is at 0.1A·g -1 The constant current charge and discharge curve diagram below.
[0036] Figure 8 This is the impedance diagram of the aluminum ion battery in Example 3 of the present invention.
[0037] Fig. 9 This is the GITT diagram of the aluminum ion battery in Example 3 of the present invention under different charge and discharge conditions. DETAILED DESCRIPTION
[0038] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with various embodiments.
[0039] Example 1
[0040] This embodiment provides an organic electrode material (Nqphen), which is obtained by a one-step dehydration condensation reaction of 1,10-phenanthroline-5,6-dione and 2,3-diaminonaphthalene-1,4-dione, and its molecular structure is as follows:
[0041]
[0042] The preparation process of the organic electrode material in this embodiment is as follows:
[0043] Weigh 1 mmol of 1,10-phenanthroline-5,6-dione, 1.2 mmol of 2,3-diaminonaphthalene-1,4-dione and 150 mL of ethanol / acetic acid (the volume ratio of ethanol to acetic acid is 1:1) respectively and add them into a 250 mL three-necked flask, and ultrasonically treat for 15 minutes until the solid is completely dissolved. Then, put the three-necked flask into an oil bath for stirring and heating. The reaction conditions are 70°C, 200 rpm, and the reaction time is 12 hours. The relevant reaction formula is as follows: Figure 1 shown.
[0044] After the reaction is complete, cool to room temperature, filter and wash with ethanol, acetic acid and water in sequence to obtain a light yellow solid (target solid), and finally dry in a vacuum oven.
[0045] Figure 2 The Fourier transform infrared spectrum of the organic electrode material obtained in this example shows that the absorption peak of the stretching vibration of the -NH2 bond of Nq disappears; at the same time, the retention of the C=N bond in phen and the appearance of the C=O bond prove that the synthesis of Nqphen is successful.
[0046] Figure 3 This is the thermogravimetric analysis diagram of the organic electrode material obtained in this example. It can be seen that it has good structural thermal stability.
[0047] Figure 4 This is a scanning electron microscope image (scale: 10.0 μm) of the organic electrode material obtained in this example. It can be seen from the image that it has a uniform flaky structure.
[0048] Example 2
[0049] The difference from Example 1 is that in this example, 0.8 mmol of 1,10-phenanthroline-5,6-dione, 1 mmol of 2,3-diaminonaphthalene-1,4-dione and 120 mL of ethanol / acetic acid (volume ratio of 1:1) are weighed and added to a 250 mL three-necked flask, and ultrasonic treatment is performed for 10 minutes until the solid is completely dissolved. Then, the three-necked flask is placed in an oil bath for stirring and heating, and the reaction conditions are 80°C, 150 rpm, and the reaction time is 10 hours. The remaining steps and parameters are the same as those in Example 1.
[0050] The organic electrode material obtained in this example also has good structural thermal stability and a uniform sheet structure.
[0051] Example 3
[0052] This embodiment provides a high-performance aqueous aluminum ion battery, wherein the positive electrode sheet is prepared using the organic electrode material (Nqphen) obtained in Example 1, and the specific process is as follows:
[0053] 1. Preparation of positive electrode sheet:
[0054] Nqphen, Ketjen black and polyvinylidene fluoride (the weight ratio of the three is 7:2:1) are weighed respectively and put into an agate mortar, then 5 ml of N-methyl-2-pyrrolidone is added, and the slurry is continuously ground to form a uniform slurry, which is then evenly coated on the titanium foil current collector, and finally placed in a vacuum oven at 80-100°C and dried for 20-26 hours to make a positive electrode sheet.
[0055] 2. Battery preparation:
[0056] The positive electrode sheet was used as the positive electrode, the aluminum foil was used as the negative electrode, and the glass fiber separator was used as the separator between the positive and negative electrodes to separate the electrodes. 1M Al(ClO4)3 electrolyte was added to assemble a button battery.
[0057] Figure 5 The aluminum ion battery obtained in this example has a -1 Cyclic voltammetry curves at different scan rates. It can be seen that it has two pairs of obvious redox peaks, and the peak shapes at different cycle numbers are exactly the same, indicating that the aluminum ion battery has good reversibility.
[0058] Figure 6 The rate performance diagram of the aluminum ion battery obtained in this example is shown in the figure. It can be seen from the figure that at 0.1, 0.15, 0.2, 0.3, 0.4, 0.5, 0.7 and 1.0 A·g -1 At current densities of 1.3, 1.7, 2.1, 1.9, 2.1, 2.2, 3.5, 4.9, 5.3, 6.9, 7.9, 8.8, 9.9, 10.1, 11.3 mAh·g -1 When the current density returns to 0.1A·g -1 When the battery is charged, the specific capacity of the battery can be restored to its original value, indicating that the positive electrode material used in this embodiment has high reversibility.
[0059] Figure 7 The aluminum ion battery obtained in this example is 0.1A·g -1 The constant current charge-discharge curve diagram is shown below. According to the charge-discharge curve, it can be seen that the positive electrode material used in this embodiment exhibits a higher initial specific capacity and has a clear charge-discharge platform, which corresponds to the cyclic voltammetry curve.
[0060] Figure 8 The impedance diagram of the aluminum ion battery obtained in this example is shown in Figure 1. It can be seen that the charge transfer impedance (Rct, the semicircle diameter in the high frequency band) of the aluminum ion battery is small, indicating that it has the ability of rapid charge transfer.
[0061] Fig. 9 The GITT diagram of the aluminum ion battery obtained in this example under different charge and discharge conditions is shown in Figure 1. It can be seen from the GITT diagram that under different charge and discharge conditions, the cation has a high diffusion coefficient, indicating that the aluminum ion battery has a high ion diffusion coefficient.
[0062] In summary, the present invention designs an organic electrode material, which has C=O and C=N as active sites to give it a high reversible capacity and a fast charge transfer capability, and these characteristics make the organic electrode material show great potential when applied to positive electrode materials of aluminum ion batteries. Therefore, compared with the prior art, the present invention has a very obvious technical progress, outstanding substantive characteristics and significant progress.
[0063] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.
Claims
1. An organic electrode material, characterized in that The molecular structure of the organic electrode material is:
2. The method for preparing the organic electrode material according to claim 1, characterized in that: It is obtained by one-step dehydration condensation reaction of 1,10-phenanthroline-5,6-dione and 2,3-diaminonaphthalene-1,4-dione.
3. The method for preparing an organic electrode material according to claim 2, characterized in that: The specific process of the one-step dehydration condensation reaction is as follows: Step 1: adding 1,10-phenanthroline-5,6-dione and 2,3-diaminonaphthalene-1,4-dione to an ethanol / acetic acid solution with a volume ratio of 1:1, and ultrasonically treating until the solid matter is completely dissolved to obtain a mixed solution; the molar ratio of the 1,10-phenanthroline-5,6-dione to the 2,3-diaminonaphthalene-1,4-dione is 0.8-1:1-1.2; Step 2: Stir and heat the mixed solution to allow 1,10-phenanthroline-5,6-dione and 2,3-diaminonaphthalene-1,4-dione to react completely, and then cool to room temperature; Step 3: The solution obtained in step 2 is filtered to obtain the target solid, which is then washed and dried to obtain the organic electrode material.
4. The method for preparing an organic electrode material according to claim 3, characterized in that: In the step 2, the reaction conditions are 70-80° C. and 150-200 rpm.
5. The method for preparing an organic electrode material according to claim 4, characterized in that: In the step 3, after the suction filtration, the target solid is washed with ethanol, acetic acid and water in sequence.
6. A high-performance aqueous aluminum ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The positive electrode is made of the organic electrode material according to claim 1.
7. The high performance aqueous aluminum ion battery according to claim 6, characterized in that: The preparation process of the positive electrode is as follows: Step a: mixing and grinding an organic electrode material, a conductive agent and a binder in a weight ratio of 7:2:1 to form a uniform slurry; Step b: The slurry is evenly coated on the titanium foil current collector, and then dried to obtain the positive electrode.
8. The high performance aqueous aluminum ion battery according to claim 7, characterized in that: The step a is specifically as follows: weighing the organic electrode material, the conductive agent and the binder respectively and putting them into an agate mortar, then dropping 2-5 ml of N-methyl-2-pyrrolidone therein, and continuously grinding to form a uniform slurry.
9. The high performance aqueous aluminum ion battery according to claim 7 or 8, characterized in that: The conductive agent is Ketjen black.
10. The high performance aqueous aluminum ion battery according to claim 9, characterized in that: The binder is polyvinylidene fluoride.
Citation Information
Patent Citations
Carboxyl-containing bipyridino phenazine organic compound as well as preparation method and application thereof
CN115260196A
Phenazine aqueous positive electrode material and preparation method and application thereof
CN118406053A